Seminal Attributes And Their Relation With Scrotal Biometry And Sexual Behaviour Of Murrah Buffalo Bull - Singh, A.K.; Shukla, S.P.; Pandey, S.S.; Misraulia, K.S.; Kumar , Sudarshan (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted on 32 Murrah buffalo bulls to evaluate the seminal attributes and their relation with scrotal biometry and sexual behavior of Murrah buffo bull . There was significant (P<0.05) positive correlation between scrotal circumference with age, ejaculate volume, mass activity and sperm concentration. There was non- significant negative correlation of sexual behaviour with age and positive correlation with sperm concentration. Murrah buffalo bulls around the age of 5.0-6.5 year exhibit maximum sexual desire, however, maximum scrotal circumference for the age of more than 6.5 years was observed.